2018
DOI: 10.1073/pnas.1805784115
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the COPII gene paralogs SEC23A and SEC23B are interchangeable in vivo

Abstract: Approximately one-third of the mammalian proteome is transported from the endoplasmic reticulum-to-Golgi via COPII-coated vesicles. SEC23, a core component of coat protein-complex II (COPII), is encoded by two paralogous genes in vertebrates ( and ). In humans, SEC23B deficiency results in congenital dyserythropoietic anemia type-II (CDAII), while SEC23A deficiency results in a skeletal phenotype (with normal red blood cells). These distinct clinical disorders, together with previous biochemical studies, sugge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 64 publications
4
85
0
Order By: Relevance
“…Recent characterizations of mice with genetic deficiency of COPII components have extended these findings to mammalian physiology, revealing a variety of complex phenotypes [8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent characterizations of mice with genetic deficiency of COPII components have extended these findings to mammalian physiology, revealing a variety of complex phenotypes [8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…As the coat proteins serve essential roles in all tissues and cells, the reason for the erythroid-specific phenotypes is not clear. It has recently been suggested that in human (but not in mouse) SEC23B is highly expressed in the erythroid system and thus uniquely affects this system [3]. The key CDA type III characteristic is giant multinucleate erythroblasts with up to 12 nuclei per cell.…”
Section: Introductionmentioning
confidence: 99%
“…This result leads to the question of why the paralogues identified in this study were retained. One possibility is that multiple copies of a gene may be retained simply because their promoters lose effectiveness in different cell types or developmental stages . For example, the two paralogues of the Sec23 subunit of COat Protein complex II (COPII) in mammalian cells, which originated from a duplication occurring early in vertebrate evolution, have different tissue‐specific expression patterns, but indistinguishable interactomes .…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that multiple copies of a gene may be retained simply because their promoters lose effectiveness in different cell types or developmental stages . For example, the two paralogues of the Sec23 subunit of COat Protein complex II (COPII) in mammalian cells, which originated from a duplication occurring early in vertebrate evolution, have different tissue‐specific expression patterns, but indistinguishable interactomes . A corollary of this is that although there may be multiple paralogues present for a given complex subunit, they may not be expressed simultaneously in the same cells, therefore perhaps contributing little to complexity at the cellular level.…”
Section: Discussionmentioning
confidence: 99%